2011
DOI: 10.1590/s1413-41522011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da toxicidade de Cr (VI) e Zn (II) no crescimento do fungo filamentoso Aspergillus niger isolado de efluente industrial

Abstract: Processos convencionais de tratamento de efluentes utilizam microrganismos vivos, o que sugere limitações relativas À toxicidade de metais para os microrganismos. O experimento consistiu em adicionar soluções monoelementares de Cr (VI) e Zn(II) em diferentes concentrações (0, 20, 50, 100, 200, 300, 400, 500 mg.L-1) ao meio de crescimento e observar a influência dos metais no crescimento micelial e germinativo do fungo Aspergillus Níger por verificação visual da expansão radial do micélio e da germinação de esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…The test was performed in triplicate. Growth was observed at 24, 48, 72, and 96 h. Inhibition of mycelial growth (PIC) was calculated by Equation: (%) PIC = RGC -RGT ∕ RGC × 100, where RGC = radial growth of control (cm) and RGT = radial growth of treatment (cm) (Vale et al, 2011).…”
Section: Activity Of Trichoderma Sspmentioning
confidence: 99%
“…The test was performed in triplicate. Growth was observed at 24, 48, 72, and 96 h. Inhibition of mycelial growth (PIC) was calculated by Equation: (%) PIC = RGC -RGT ∕ RGC × 100, where RGC = radial growth of control (cm) and RGT = radial growth of treatment (cm) (Vale et al, 2011).…”
Section: Activity Of Trichoderma Sspmentioning
confidence: 99%
“…Several compounds, including crude oil, naphthalene, phenanthrene, anthracene, fluoranthene, pyrene, benzo(a)pyrene (Da Silva, Umbuzeiro, Pfenning, Canhos, & Esposito, 2003;Argumedo-Delira, Alarcon, Ferreira-Cerrato, Almaraz, & Peña Cabriales, 2012;Lee et al, 2014;Zafra, Absálon, Cuevas, & Cortes-Espinosa, 2014), triazine herbicides (Colla, Primaz, Lima, Bertolini, & Costa, 2008) and heavy metals (Vale, Abreu, Gouveia, Leitão, & Santaella, 2011), has been used in these types of tests. The literature reports that high growth rates and tolerance to certain levels of contaminants are considered desirable characteristics in microorganisms, as are indicators of an ability to degrade such xenobiotics as PAHs (Lamar, Larsen, & Kirk, 1990;Matsubara, Lynch, & De Leij, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to Vale et al (2011), an Aspergillus niger strain was able to develop in culture medium supplied with growing concentrations of Zn and Cr until 100 mg. L -1 . Authors found that ion Cr showed higher toxicity than ion Zn, inhibiting the capacity of the fungus to develop during the germinative phase.…”
Section: Resultsmentioning
confidence: 99%